Effects of Essential Oils in the Treatment of Acute Rhinosinusitis: A Systematic Review - Christina M. Matl; Wooyoung Jang; Jordan R. Salley; Callie L. Fort; Joshua C. Demke; Phat Tran; James C. Wang (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Basic science studies have shown that essential oils have antibacterial and anti‐inflammatory effects in the nasal mucosa. However, clinical studies examining the effect of essential oils on patient outcomes are limited. The aim of this systematic review is to evaluate the patient outcomes following treatment of acute rhinosinusitis with essential oils. Methods PubMed, Ovid, Cochrane, and Embase computerized searches were performed to include results published up to December 2023. Two independent reviewers (C.M.M. and W.J.) conducted data extraction following a predetermined protocol, with any discrepancies reviewed by the senior author (J.C.W.). Results Five RCTs investigated the treatment of rhinosinusitis with essential oils in capsule form. Essential oils included in the studies were Cineole, Myrtol (ELOM‐080), Sinupret (BNO 1016), and Tavipec. Significant improvements in rhinological symptoms were seen in Cinole compared to placebo, Cinole compared to an herbal compound similar in composition to Sinupret, Tavipec compared to placebo, and ELOM‐080 compared to placebo. Outcome measures included nasal obstruction, nasal drainage, facial pressure, headache, fatigue, and fever. Little difference in patient‐reported rhinological symptom improvement was seen in ELOM‐080 compared to BNO 1016 using a 5‐point Likert Scale. Minimal adverse effects were observed in patients treated with essential oils with the most common adverse effect being mild gastrointestinal upset. Conclusion Patients using essential oils reported improvement in acute rhinosinusitis symptoms in all studies reviewed, despite differences in methodology and outcome measures. These improvements were statistically significant in all the studies. Level of Evidence Level 1 based on “The Oxford 2011 Levels of Evidence”.